Pengembangan Alat Evaluasi Pembelajaran Berbasis Two Tier Multiple Choice Dengan Menggunakan Aplikasi Quizizz - Nur Ana Asiana; Sri Uchtiawati; Sri Suryanti (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study is to develop a two tier multiple choice evaluation tool using the quizizz application to determine the results of learning mathematics. The research model used is 4D. The test subjects in this study using IX-B class of Nurul Huda Leran junior high school. The research instruments used were interview sheets, validation sheets, test instruments, and questionnaires. Data analysis techniques using quantitative and qualitative analysis. The results of this research are the evaluation tool is feasible because it meets 2 criteria valid and effective. The valid criteria based on the assessment of media experts by 84% (very feasible) and material experts by 91% (very feasible). Effective criteria seen of student responses and the quality of items. The results of student responses obtained 94% (very interesting). While the quality of the items, the validity test of all 10 questions is valid. the reliability test, there is 1 question that is not reliable then no used, so that only 9 question are used. the difficulty level test, there are 7 questions in the medium categori, 3 question in the easy category, and there are no question in the difficult category. In the discriminatory test there are 2 question in the very good category, 5 question in the good category, 3 questions in the sufficient category, and not question in the bad category. the effectiveness of the distractor, there is 1 distractor option selected of all students.